Microfiltración apical utilizando la técnica de condensación lateral y Sistema BeeFill TM 2 EN 1. Estudio in vitro - Castillo Stoll, Luis Orlando (2011)
This research aims to compare the in vitro apical microleakage between lateral condensation and System TM BeeFill 2 in 1. Chemomechanical were prepared with 5.25% sodium hypochlorite and EDTA to remove the smear layer, single-rooted premolars of 50 straight pipes and unique and were randomized into four groups: two experimental groups of 20 pieces each, sealed with the lateral condensation technique BeeFill system TM 2 in 1, a positive control group and a negative control group of five pieces each, not sealed. All parts were dried five days and then placed a layer of enamel on the root surface except the apical 4 millimeters. The negative control group as a whole is varnished. They were then immersed in test tubes with black India ink neutral pH and placed in the centrifuge for 5 minutes at 3000 rpm and passive immersion for three days at 37 oC. Were washed by removing the remains of nail polish with a scalpel. Then he proceeded to the demineralization of the teeth in 5% nitric acid for 48 hours. Then dehydrated in ascending alcohol at 80 degrees, 90 degrees and 100 degrees for 5 hours each and finally in methyl salicylate for 48 hours. Microfiltration was measured by the stereomicroscope and millimeters. To determine whether a difference exists in the in vitro apical microleakage using lateral condensation technique and system BeeFill TM 2 in 1, according to the research hypotheses, we used the t test for bilateral comparison of averages, to evaluate the assumptions of normality by the test Kolmogorov-Smirnov and Levene test for homogeneity of the groups compared. The results showed no significant difference in apical microleakage using lateral condensation and System BeeFill TM 2 in 1 (p> 0.05).